2008
DOI: 10.1055/s-0028-1085448
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Olympus EndoArm for Spinal and Skull-based Transsphenoidal Neurosurgery

Abstract: Minimally invasive surgical techniques have evolved to reduce soft-tissue injury associated with open surgical techniques. The use of endoscopic visualization allows the exposure of deep structures and provides a mechanism to perform all the components of an open surgical procedure through small portals, thus satisfying a basic requirement of minimally invasive surgical procedures. Surgeons in the field of skull-base and spine surgery are now taking advantage of the benefits of such endoscopes. The pneumatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…Because there are two relatively wide nasal cavities, a one‐handed operation can be avoided if an endoscope is inserted through one cavity and forceps through the other. It has been reported that a two‐handed procedure can be performed by fixing the endoscope for spinal or cranial base transsphenoidal neurosurgery . When ear surgery is performed it is possible to insert one endoscope and two forceps at the same time, but this means that the working space becomes inadequate because of the narrow external auditory canal.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are two relatively wide nasal cavities, a one‐handed operation can be avoided if an endoscope is inserted through one cavity and forceps through the other. It has been reported that a two‐handed procedure can be performed by fixing the endoscope for spinal or cranial base transsphenoidal neurosurgery . When ear surgery is performed it is possible to insert one endoscope and two forceps at the same time, but this means that the working space becomes inadequate because of the narrow external auditory canal.…”
Section: Discussionmentioning
confidence: 99%
“…This allows both hands to be free. [45] The management of intradural bleeding can be done with the use of a thrombin-gelatin haemostatic matrix. [46] A high definition (HD) camera is much superior to standard three-chip camera.…”
Section: Techniquementioning
confidence: 99%
“…Viele Operateure benutzen als "dritte Hand" spezielle, z. B. pneumatisch betriebene, flexible Halte-Arme für das Endoskop [37,100,116,329,330,[353][354][355][356][357][358]. Andere verwenden diese Halter nur in einzelnen Phasen der OP oder nur bei ausgewählten Eingriffen wie z.…”
Section: Instrumente Vorbereitung Zur Anaesthesie Monitoringunclassified